2014
DOI: 10.1186/1476-511x-13-129
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D receptor gene polymorphisms with metabolic syndrome: a case–control design of population-based cross-sectional study in North China

Abstract: BackgroundMetabolic syndrome (MS) increases a risk of developing cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM). The Vitamin D Receptor gene (VDR) may be important for developing MS. The aim of this study is to investigate the correlation between the VDR gene polymorphisms and MS in North China.MethodsA case–control study included 391 participants with MS according to the MS diagnostic criteria of International Diabetes Federation 2005 (IDF2005) and 400 controls was conducted on the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 38 publications
2
23
2
Order By: Relevance
“…Of these, 14 case–control studies examined the association of the ApaI rs7975232 (G > T) variant [ 3 , 18 30 ] (Table 1 ), 22 studies in 20 case–control papers examined the association of the BsmI rs1544410 (A > G) variant [ 18 , 22 , 23 , 27 39 ] (Table 2 ), 19 studies in 18 case–control studies examined the association of the Taq1rs731236 (T > C) variant[ 3 , 18 28 , 32 , 33 , 35 , 38 – 40 ] (Table 3 ) and 18 studies in 16 case–control studies in15 papers examined the association of FokIrs2228570 (C > T)variant [ 3 , 18 , 23 25 , 27 , 30 32 , 36 , 41 45 ] (Table 4 ) with Insulin resistance related diseases susceptibility.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 14 case–control studies examined the association of the ApaI rs7975232 (G > T) variant [ 3 , 18 30 ] (Table 1 ), 22 studies in 20 case–control papers examined the association of the BsmI rs1544410 (A > G) variant [ 18 , 22 , 23 , 27 39 ] (Table 2 ), 19 studies in 18 case–control studies examined the association of the Taq1rs731236 (T > C) variant[ 3 , 18 28 , 32 , 33 , 35 , 38 – 40 ] (Table 3 ) and 18 studies in 16 case–control studies in15 papers examined the association of FokIrs2228570 (C > T)variant [ 3 , 18 , 23 25 , 27 , 30 32 , 36 , 41 45 ] (Table 4 ) with Insulin resistance related diseases susceptibility.…”
Section: Resultsmentioning
confidence: 99%
“…There are assumptions suggesting, that genotype FF for the FokI polymorphism was correlated with lower BMI in subjects with metabolic syndrome (Zhao et al, 2014). The FokI polymorphism may modify BMI, while the BsmI polymorphism seems to influence waist circumference.…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs), including rs1544410 ( BsmI ), rs7975232 ( ApaI ), and rs731236 ( TaqI ), located at the 3′ untranslated region of VDR gene have been shown to influence mRNA stability and VDR expression ( 22 , 46 ) whereas rs2228570 ( FokI ) SNP located near the promoter region results in altered VDR activity due to change in amino acid sequence of this protein ( 47 ). Genetic variants in VDR gene have been reported to be associated with MS and its components including anthropometric parameters related to obesity, insulin resistance, T2DM, and atherogenic lipid abnormalities in different populations ( 21 , 23 , 48 ). In contrast to these data, some studies have demonstrated no association between VDR gene polymorphisms and the risk for MS development ( 49 51 ).…”
Section: Discussionmentioning
confidence: 99%